LEGAL AWARENESS AS A KEY OF FORMING A LAW CULTURE - Varava, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to carry out a theoretical analysis of the phenomena of «legal consciousness» and «legal culture», to determine the main features, structure of legal consciousness and bring its classification. And also: analysis of the main factors and features of the formation of legal awareness as a factor in the development of legal culture in Ukraine; identification of pedagogical problems and practical issues related to the formation of the legal culture of youth and future lawyers in particular. Research methods: it is based on the dialectical method, the method of analysis, comparison and synthesis, as well as the method of historicism, which allow to identify the inner essence of phenomena through the characteristics of the dynamics of their development and external manifestations; an integrated approach to creating a theoretical picture of the object is important. Results: the essence of the definitions of «legal culture» and «legal consciousness» is clarified, the main features of legal consciousness are singled out, its structure is determined and the classification is given. Theoretical analysis of the phenomena «legal consciousness» and «legal culture» was carried out. The problems of formation of legal culture of youth are defined and the theoretical approach for their decision by influence on legal consciousness of citizens is offered. It is established that one of the most important stages in the formation of legal awareness in society is legal education, which is mostly implemented through the educational activities of educational institutions and law enforcement agencies, which are designed to form legal awareness and lawful behavior. The current state of Ukrainian society is analyzed and the ways of forming the legal consciousness of citizens are studied. The author argues that building a democratic state governed by the rule of law is impossible without a sufficient level of legal awareness of the population. The thesis is argued that legal consciousness has a multicomponent nature due to the fact that it reflects a set of qualities inherent in the processes and phenomena of the legal branch of society. The development of legal culture and legal awareness was further developed. Discussion: argues that the public awareness of the public is the social security of the rule of law, the only factor that can shape and ensure the state and legal order. Therefore, legal awareness needs constant rational improvement.